Peran Kinerja Pengelolaan dalam Mendorong Keberlanjutan Ekowisata di Kebun Raya Indrokilo Boyolali - Nida Muthi’ah; Mursariningsih Mursariningsih; Natna Zahra Septina Z; Unna Ria Safitri (MASMAN Master Manajemen, 2026)
Indrokilo Botanical Garden in Boyolali is an environment-based tourism area that serves strategic functions as an ex-situ conservation institution, as well as a center for education, research, and knowledge-based recreation. However, its management still faces challenges in maintaining a balance between tourism development and conservation mandates. This study aims to analyze the role of management performance in promoting ecotourism sustainability at Indrokilo Botanical Garden from environmental, social, and economic perspectives. The research employed a qualitative descriptive approach. Data were collected through field observations and in-depth interviews with purposely selected informants, including management authorities, field officers, local community members, and visitors. The findings indicate that management performance at Indrokilo Botanical Garden has been relatively effective in daily operational activities, such as site maintenance and visitor services. Nevertheless, limitations remain in long-term strategic planning, human resource capacity development, and the active involvement of local communities as management partners. These constraints have resulted in the suboptimal implementation of conservation and educational functions. The study demonstrates that management performance plays a crucial role in determining ecotourism sustainability by ensuring a balance between environmental protection, social benefits, and economic viability. Therefore, strengthening management performance is essential to support sustainable ecotourism development at Indrokilo Botanical Garden.